2022
DOI: 10.3390/d14070544
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding and Species Delimitation for Dogfish Sharks Belonging to the Squalus Genus (Squaliformes: Squalidae)

Abstract: The Squalus genus comprises a group of small demersal sharks occurring circumglobally, popularly known as dogfish sharks. This genus exhibits a conserved morphology, thus making correct morphological identification difficult. Considering these taxonomic problems and the scarcity of molecular data, the present study aimed to identify Squalus genus MOTUs, using DNA barcoding for species delimitation via ABGD (automatic barcode gap discovery), PTP (Poisson tree process), and GMYC (general mixed Yule coalescent) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…As concerns the quite divergent sequences retrieved in public repositories, obtained from specimens caught outside the Mediterranean Sea, they were analyzed using several species delimitation methods, recently applied to other elasmobranch species to address identification issues and solve taxonomic uncertainties [ 3 , 6 , 7 , 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…As concerns the quite divergent sequences retrieved in public repositories, obtained from specimens caught outside the Mediterranean Sea, they were analyzed using several species delimitation methods, recently applied to other elasmobranch species to address identification issues and solve taxonomic uncertainties [ 3 , 6 , 7 , 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, sharks belonging to the Squalus genus exhibit conserved body morphology, making identification based entirely on morphological characters complicated, leading to misidentifications [110]. This complexity is amplified even similarly via the high overlap of morphological characters among species, as identification is often based on limited and insufficiently consistent characters, like the number of vertebrae and morphometric data [10,16,20,38,111,112]. In fact, morphological and biological similarities among squalids have led to considerable confusion over their taxonomy [14].…”
Section: Taxonomic Statusmentioning
confidence: 99%
“…However, in a review of Japanese Squalus, S. blainville was defined as a species with high dorsal fins and long dorsal-fin spines [116]. The same review revealed that Squalus, referring to S. fernandinus and S. blainville by some authors, had short dorsal-fin spines and were more similar to S. mitsukurii from Japan, and suggested that nominal S. blainville from New Zealand could be identical to S. mitsukuri [112,117]. It was also noted that dogfish resembling S. mitsukurii occurred in Australia and New Zealand [31].…”
Section: Taxonomic Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Total DNA was extracted from 31 S. albicaudus samples obtained from individuals sampled from 3 different northeast and southeast Brazilian coast locations, namely Recife, in the state of Pernambuco (n = 14), Angra dos Reis, in the state of Rio de Janeiro (n = 4), and Santos, in the state of São Paulo (n = 13) (see Supplementary Figure S1). Fin and muscle samples preserved in 96% ethanol deposited at the Laboratory of Fish Biology and Genetics (LBP), UNESP, fish collection in Botucatu, SP, Brazil, were identified by the DNA barcode technique [46]. Due to the species demersal habits, captures are not frequent and most samples were obtained from local fishers and research collaborators.…”
Section: Sample Collection and Dna Extractionmentioning
confidence: 99%